Returning to ceremony : spirituality in Manitoba Métis communities - Fiola, Chantal, 1982- (Winnipeg, Manitoba : University of Manitoba Press, 2021)
"Returning to Ceremony is the follow-up to Chantal Fiola's award-winning Rekindling the Sacred Fire and continues her ground-breaking examination of Métis spirituality, debunking stereotypes such as "all Métis people are Catholic," and "Métis people do not go to ceremonies." Fiola finds that, among the Métis, spirituality exists on a continuum of Indigenous and Christian traditions, and that Métis spirituality includes ceremonies. For some Métis, it is a historical continuation of the relationships their ancestral communities have had with ceremonies since time immemorial, and for others, it is a homecoming - a return to ceremony after some time away. Fiola employs a Métis-specific and community-centred methodology to gather evidence from archives, priests' correspondence, oral history, storytelling, and literature. With assistance from six Métis community researchers, Fiola listened to stories and experiences shared by thirty-two Métis from six Manitoba Métis communities that are at the heart of this book. They offer insight into their families' relationships with land, community, culture, and religion, including factors that inhibit or nurture connection to ceremonies such as sweat lodge, Sundance, and the Midewiwin. Valuable profiles emerge for six historic Red River Métis communities (Duck Bay, Camperville, St Laurent, St François-Xavier, Ste Anne, and Lorette), providing a clearer understanding of identity, culture, and spirituality that uphold Métis Nation sovereignty."--
Cover -- Contents -- Note on Terminology -- Map of Métis Communities -- Introduction. Métis Spirituality: Confronting Stereotypes -- Chapter 1. Searching for Our Stories in Oral History -- Chapter 2. Combing the Written Record for Our Stories -- Chapter 3. A Métis-Centred Study and Approach -- Chapter 4. Six Red River Métis Communities -- Chapter 5. Meeting the Participants -- Chapter 6. Métis Family Relationships with Land, Language, and Identity -- Chapter 7. Métis Family Relationships with Culture and Religion -- Chapter 8. Exploring Self-Identification -- Chapter 9. Spirituality, Types of Ceremonies, and Disconnection Factors -- Chapter 10. Spiritual Connection Factors, Impacts upon Identity, and Others' Reactions -- Chapter 11. Métis Spirituality Today -- Gichi-Miigwetch (Acknowledgements) -- Glossary -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 30, 2021).
eBooks on EBSCOhost
Keywords: Métis -- Manitoba -- Rites and ceremonies; Métis -- Manitoba -- Religion; Métis -- Manitoba -- Social life and customs; Métis -- Manitoba -- Ethnic identity; Nation Métis -- Manitoba -- Rites et cérémonies.; Nation Métis -- Manitoba -- Religion; Nation Métis -- Manitoba -- Mœurs et coutumes; Nation Métis -- Manitoba -- Identité ethnique; SOCIAL SCIENCE / Ethnic Studies / Native American Studies; Métis -- Ethnic identity; Métis -- Social life and customs; Manitoba